Effect of Stirrups on the Behavior of Semi-Precast Concrete Slabs - Mazin Diwan Abdullah; Khamail Abdul-Mahdi Mosheer (Civil Engineering Journal, 2022)
A semi-slab of precast concrete (or half-slab) is a structural system that consists of concrete at the bottom half of a slab and concrete cast in situ at the top. To avoid traditional formwork and minimize the bottom half of the slab, this section can function as formwork and reduce the thickness of precast slabs, which makes their transportation easy. The interface between precast and overtopping concrete is effective for the slab system's performance. To improve the half-slab floor system, it is needed to have a shear connector (stirrups). Therefore, to better understand the behavior of this slab system, six full-scale slab specimens (2×7.5 m) with different shapes of the stirrups and spacing between them were constructed for this study. One specimen was produced with no connections and served as a reference specimen, while the other employed stirrups to connect slab units. The tests found that the distribution and type of stirrups affect the structural performance of the semi-precast concrete slab. The maximum load capacity of slabs with rectangular or triangular connections was nearly more significant than reference slabs, reaching 136.11 and 86.11%, respectively. The maximum load increased by 81.4 % for rectangular connections and 54.9% for triangular connections when the distance between the connectors was reduced from 600 to 300 mm. Furthermore, stirrups in semi-precast slabs could improve the cracking behavior, stiffness, and ductility. Doi: 10.28991/CEJ-2022-08-08-09 Full Text: PDF